An Unknown English Translation of Virgil's Third Georgic (c.1800). (November 2015) - Gillespie, Stuart
Abstract : This article supplies the 757 lines of this never-before-printed translation into English couplet verse found in BL MS Add. 38448A. The author's identity is currently unknown, but circumstantial detail suggests that Robert Jenkinson, the second Lord Liverpool, was his patron. An introduction explains the manuscript's context and probable date.